Live Imaging of Silver Nanostructures Electrochemically Dissolving at Open-Circuit Potential - Körner, Andreas; Morales, A. Lucía; Fritsch, Birk; Fiedler, Lena; Mulvey, Justin T.; Göllner, Christian; Alloyeau, Damien; Patterson, Joseph P.; Malgaretti, Paolo; Mayrhofer, Karl J.J.; Cherevko, Serhiy; Hutzler, Andreas (Small, 2026)
The stability of electrode and electrocatalyst materials is of paramount importance for sustainable and persistent technological solutions for energy conversion systems. In fact, dissolution of electrodes at open-circuit potential occurs both during electrochemical testing operando and using a scanning flow cell-inductively coupled plasma-mass spectrometry (SFC-ICP-MS) setup. Although these phenomena occur frequently, their mechanisms remain concealed. This is because structural changes occur at the nanoscale, which are difficult to observe directly. Herein, we introduce a workflow comprising automated image analysis, beam effect assessment, and correlative electrochemical testing to obtain quantitative and representative data from electrochemical liquid phase electron microscopy (EC-LP-EM). In a demonstrator experiment, we reveal that the dissolution of silver electrodeposited on a platinum electrode substrate is driven by system equilibration involving the oxygen reduction reaction and bimetallic corrosion. This combination of reactions occurs at the electrode-electrolyte interface under zero net current conditions as an example of structural changes on the nanoscale during operation. Our experimental findings, furthermore, serve as a blueprint for correlating nanoscale live imaging information with macroscopic electrochemical responses to investigate degradation mechanisms of electrocatalysts and materials beyond. These insights aid in designing efficient electrochemical conversion systems, urgently needed in renewable energy technology.
CRIS-Team Scopus Importer:2026-02-13
Keywords: bimetallic corrosion; correlative electrochemistry; degradation mechanisms; liquid phase electron microscopy; nanocorrosion; open-circuit potential; radiolysis assessment